Exhaled nitric oxide in endurance athletes during exercise in normoxia and hypoxia - Verges, S.; Flore, P.; Favre-Juvin, A.; Lévy, P.; Wuyam, B. (2005)
Resümee des Vortrags auf dem Zweiten Symposium Höhenphysiologie und Praxis am Fuße des Watzmann, August 2005 Aim. Endogenous nitric oxide (NO) through its relaxing effect on smooth muscle cells may be involved in pulmonary gas exchange as well as in the modulation of the hypoxic pulmonary vasoconstriction. As athletes with exercise-induced hypoxemia (EIH) present pulmonary gas exchange abnormalities in normoxia that could be even greater in hypoxia, we hypothesised that pulmonary NO may be lower in such athletes with EIH. Methods. Eleven athletes with EIH [decrease in arterial oxygen blood partial pressure (PaO2) >12 mmHg] and nine without EIH (N.EIH) exercised at 40%, 60% (10 min) and 90% (5 min) of normoxic maximal power output (Pmax) in normoxia, and at 40% and 60% (10 min) of Pmax in hypoxia (FiO2=15%). Exhaled NO concentration during a constant flow exhalation (FENO0.170) and arterialized blood gases were measured at every power output. Results. FENO0.170 decreased from rest to exercise both in normoxia (-27.8±22.8% at 90%Pmax, P<0.001) and hypoxia (-23.8±17.5% at 60%Pmax, P<0.001). At 90%Pmax in normoxia, EIH athletes showed lower PaO2 (76.7±5.4 vs. 82.8±4.4 mmHg, P=0.013) and greater FENO0.170 decrement (-37.0±24.7% vs. -16.6±14.6%, P=0.042) than N.EIH athletes. During hypoxic exercise, PaO2 and FENO0.170 decreases were similar in both groups (P>0.05). Conclusion. The present study shows lower pulmonary NO in athletes with gas exchange abnormalities during intense exercise in normoxia, while EIH and N.EIH athletes have similar decreases in blood gases and pulmonary NO during hypoxic exercise. Decreased pulmonary NO in such conditions may contribute to ventilationperfusion inequality and/or increase pulmonary vascular tone in athletes.